Banking business models and risk: Findings from the ECB's comprehensive assessment. (18th December 2019) - Paladino, Giovanna; Rotondi, Zeno
Abstract: We use the results of the ECB's comprehensive assessment to evaluate the importance of the bank business model on risk assessment and the persuasive effectiveness of different supervisory styles on banks' recapitalization. Our analysis reveals inconsistencies in the information content provided by the various regulatory measures used for assessing bank stability. Moreover, opposite to CET1 ratio, the leverage ratio provides assessments on business models more consistent with a market‐based measure of bank risk exposure and Z‐SCORE. Accounting for several control variables both at the bank and country level, we also find evidence that the effectiveness of the supervisory action depends on the specific type of supervisory model. In particular, countries adopting the hybrid model seem more effective in persuading banks to recapitalize preventively. Differently, countries adopting the integrated and the sectorial model seem less effective in their requests.